2018
DOI: 10.18203/2349-3291.ijcp20175928
|View full text |Cite
|
Sign up to set email alerts
|

The smart phone study: assessing the reliability and accuracy of neonatal jaundice measurement using smart phone application

Abstract: Background: Current gold standard for bilirubin estimation in newborns is invasive while transcutaneous bilirubinometer which is a noninvasive option is costly. Smart phone applications can be used as an alternative to measure bilirubin. We did the study to evaluate “Biliscan” medical application for screening of neonatal jaundice.Methods: During the first seven days, neonates with suspected jaundice were taken blood samples for serum bilirubin. Within two hours photographs were taken using Biliscan app by pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 8 publications
4
35
0
5
Order By: Relevance
“…Actually, only a smartphone with a camera and a dedicated app were required. However, the accuracy of this method has been reported to vary widely, with R = 0.48 to 0.91 ( 21 , 22 , 43 , 44 ). The measurements were affected by the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, only a smartphone with a camera and a dedicated app were required. However, the accuracy of this method has been reported to vary widely, with R = 0.48 to 0.91 ( 21 , 22 , 43 , 44 ). The measurements were affected by the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published in the last few years have described novel ways of assessing neonatal jaundice by using digital images or smartphones, by adopting slightly different approaches. [11][12][13][14][15][16] Based on previous research on the bio-optical properties of newborn skin, we have developed a physics-based system that estimates bilirubin from digital images. 17 The purpose of this study was to evaluate the accuracy of this new method.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Mobile phone health (mHealth) is of interest, because even areas with scarce economic resources can use it 10 . Studies published in the last few years have described novel ways of assessing neonatal jaundice by using digital images or smartphones, by adopting slightly different approaches 11‐16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data acquired from Biliscan were compared with measures of total serum bilirubin (TSB), which is the current gold standard, as reference. It was then found that there exists a good correlation of ~0.6 between Biliscan estimates and TSB levels [73]. Additionally, Pelham et al designed a portable, accurate, and low-cost device called BiliSpec that is capable of quantifying TSB levels from small drops of whole blood applied to a lateral flow card.…”
Section: F Biomedical Engineering Solutions To Preventable Neonatal mentioning
confidence: 99%